2011
DOI: 10.5430/ijfr.v2n2p2
|View full text |Cite
|
Sign up to set email alerts
|

The Managerial Control Types of Conglomerates and Firm Performance

Abstract: This paper investigated the relationship among board leadership structure, shareholder rights, the divergence of responsibilities, and firm performance under a variety of conglomerate-controlling behaviors. Results revealed a negative correlation among chief executive officer (CEO) duality and deviations from stock-control rights, earnings-distribution rights, seat-control rights, and stock-control rights on a single family-controlled company's performance. The ratio of shares held by directors and independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…ROE serves as a metric for evaluating the efficiency of management in generating gains and growth from shareholders' investments. Scholars such as Bari et al (2021) and Chiang & Lin (2011) commonly employ ROE as an indicator of firm performance.…”
Section: The Explained Variablesmentioning
confidence: 99%
“…ROE serves as a metric for evaluating the efficiency of management in generating gains and growth from shareholders' investments. Scholars such as Bari et al (2021) and Chiang & Lin (2011) commonly employ ROE as an indicator of firm performance.…”
Section: The Explained Variablesmentioning
confidence: 99%
“…Most strategic management literature measuring firm performance, as a dependent variable, suffered from multiple problems concerning the employment of various indicators of firm performance that lacked either consensus or dimensionality. Financial or accounting-based ratios as measures for the firm performance were extensively utilized with concentrated employment of profitability measures, such as: profit margin (Jiang and Peng, 2010;Bauwhede, 2009;Premuroso and Bhattacharya, 2007), return on sales (Bøhren and Strøm, 2010;Filatotchev, Isachenkova and Mickiewicz, 2007), earnings per share (Yue, Lan and Jiang, Luan, 2008;Filatotchev, Lien and Piesse, 2005), return on equity (Ibrahim and AbdulSamad, 2011;Chaghadari, 2011;Chamberlain, 2010;Yue, Lan and Jiang, 2008;Luan and Tang, 2007), and return on assets (Chiang and Lin, 2011;Kim and Yoon, 2007;Xu, Zhu and Lin, 2005). Furthermore, more advanced SMAPs, such as BSC, were developed to help management in evaluating the firm performance from multi-focal aspects; financial and non-financial, indicators of firm performance measured more than the financial aspect of business firms.…”
Section: Firm Performancementioning
confidence: 99%
“…The theory suggests that stewards are satisfied and motivated when organizational success is attained. Stewardship theory recognizes the importance of structures that empower the steward and offers maximum autonomy built on trust (Chiang & Lin, 2011). It stresses on the position of executives to act more autonomously so that the shareholders' returns are maximized.…”
Section: Stewardship Theorymentioning
confidence: 99%
“…The study concluded that having more or less number of independent directors in the board had no bearing on the performance of Chinese listed firms. However, in a study conducted in Taiwan focusing on the link between board composition and firm performance, Chiang and Lin (2011) found that listed companies in Taiwan suffered from the divergence between stock-control rights and earnings-distribution rights, and the divergence of rights was negatively associated with firm performance. The study also found that CEO internalization was significantly positively associated with firm performance which was consistent with the viewpoint of agency theory that the controlling interests of CEO may induce them to enhance company performance.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%